Polymerase Chain Reaction for Biomedical Applications 2016
DOI: 10.5772/65742
|View full text |Cite
|
Sign up to set email alerts
|

PCR Technique for the Microbial Analysis of Inanimate Hospital Environment

Abstract: Discipline of molecular ecology and molecular techniques such as polymerase chain reaction PCR ofers a possibility to study and reveal the microbial diversity in environmental setings with complicated mixed communities, non-culturable organisms, interfering contaminants and low levels of target DNA. Hospital environment represents a new ecological niche for clinically important nosocomial pathogens and antibiotic-resistant microorganisms, which have been commonly found on various hospital surfaces. Accurate ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…The hospital environment represents a new ecological place for medically important nosocomial pathogens, antibiotic-resistant microorganisms, and reservoirs of resistance genes, which have been common, found on various surfaces within hospitals (eg medical equipment, housekeeping surfaces, workplaces and lobby (furniture). 1 , 2 Studies investigating hospital environments reported that pathogens were ubiquitous in all hospital units but the interest was usually focused on intensive care and operation unit, especially due to the vulnerability of patients in these units. 3 There is also high antibiotic usage and invasive procedure from these units.…”
Section: Introductionmentioning
confidence: 99%
“…The hospital environment represents a new ecological place for medically important nosocomial pathogens, antibiotic-resistant microorganisms, and reservoirs of resistance genes, which have been common, found on various surfaces within hospitals (eg medical equipment, housekeeping surfaces, workplaces and lobby (furniture). 1 , 2 Studies investigating hospital environments reported that pathogens were ubiquitous in all hospital units but the interest was usually focused on intensive care and operation unit, especially due to the vulnerability of patients in these units. 3 There is also high antibiotic usage and invasive procedure from these units.…”
Section: Introductionmentioning
confidence: 99%
“…Hospital environment represents a new ecological place for medically important nosocomial pathogens, antibiotic-resistant microorganisms and reservoirs of resistance gene, which have been commonly, found on various surfaces within hospitals (e.g. medical equipment, housekeeping surfaces, workplaces and lobby (furniture) [1,2]. Studies investigating hospital environments reported that pathogens were ubiquitous in all hospital units but the interest was usually focused on intensive care and operation unit, especially due to the vulnerability of patients in these units [3].…”
Section: Introductionmentioning
confidence: 99%
“…The hazard for our reputation and insurance coverage is increasing with the possibility offered by molecular biology to identify dentally acquired infections [1]. Molecular biology and in vivo biosensors technology, to detect quorum sensing signaling molecules produced by airborne pathogenic bacteria, can prove the violations and noncompliances in dental settings and useful for accreditation surveys [43][44][45][46][47]58]. Nevertheless, antimicrobial surfaces and graphene-based antimicrobial nanomaterials seem to be promising to lower cross infection [122].…”
Section: Resultsmentioning
confidence: 99%
“…Fast and very sensitive molecular biological techniques (quantitative real-time polymerase chain reaction (PCR), multiplex PCR, microarray, next-generation sequencing technologies, etc.) and in vivo biosensors technology seem to be a very promising support to improve the knowledge on bioburden and biofouling, even due to not cultivable infectious agents by classical microbiological methods, and to monitor the effectiveness of item reprocessing [43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%